Analisis Penurunan Tekanan Fluida di Dalam Pipa Antara Hotwell Pump (HWP) dan Menara Pendingin pada Pembangkit Listrik Tenaga Panas Bumi Lahendong Unit-2 - I Wayan Rikiawan; Rolles Nixon Palilingan; Alfrie Musa Rampengan (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2022)
A geothermal power plant (PLTP) is a power plant that utilizes geothermal fluid as its primary energy source. The fluid flowing in the PLTP component undergoes a change in magnitude which is very important to know, one of which is the pressure drop. Pressure drop is an essential term that can describe the pressure drop at a point in the pipe caused by particle friction in the fluid, fluid acceleration, and flow pipe elevation. An analysis of the pressure drop in the pipe between the hot well pump (HWP) and the cooling tower was carried out using the Harriston-Freeston method, which was made on Pressure Drop Modeling using a module program and visual basic. This program study the pressure drop in the pipe from the hot well pump (HWP) to the cooling tower as outlined in the form of a graph where the pressure drop along the pipe, both between hot well pump A and hot well pump B, as well as hot well pump B and cooling towers having a significant pressure drop. In the pipeline between hot well pump A and hot well pump B, the pressure is from 3.6 bar to 3.4 bar. Likewise, the pipeline between hot well pump B and the cooling tower also experiences the same pressure drop, namely at a pressure of 3.4 bar to a pressure of 1 bar. This thing is influenced by the pipe diameter. There is a reduction in diameter and particle friction in the fluid, fluid motion acceleration, and flow pipe elevation in certain pipelines.